Distal tibial pilon fractures (AO/OTA type B, and C) treated with the external skeletal and minimal internal fixation method - Milenković, Sasa Sava; Mitković, Milorad; Micić, Ivan; Mladenović, Desimir; Najman, Stevo; Trajanović, Miroslav; Manić, Miodrag; Mitković, Milan (Vojnosanitetski pregled, 2013)
Background/Aim. Distal tibial pilon fractures include extra-articular fractures of the tibial metaphysis and the more severe intra-articular tibial pilon fractures. There is no universal method for treating distal tibial pilon fractures. These fractures are treated by means of open reduction, internal fixation (ORIF) and external skeletal fixation. The high rate of soft-tissue complications associated with primary ORIF of pilon fractures led to the use of external skeletal fixation, with limited internal fixation as an alternative technique for definitive management. The aim of this study was to estimate efficacy of distal tibial pilon fratures treatment using the external skeletal and minimal internal fixation method. Methods. We presented a series of 31 operated patients with tibial pilon fractures. The patients were operated on using the method of external skeletal fixation with a minimal internal fixation. According to the AO/OTA classification, 17 patients had type B fracture and 14 patients type C fractures. The rigid external skeletal fixation was transformed into a dynamic external skeletal fixation 6 weeks post-surgery. Results. This retrospective study involved 31 patients with tibial pilon fractures, average age 41.81 (from 21 to 60) years. The average follow-up was 21.86 (from 12 to 48) months. The percentage of union was 90.32%, nonunion 3.22% and malunion 6.45%. The mean to fracture union was 14 (range 12–20) weeks. There were 4 (12.19%) infections around the pins of the external skeletal fixator and one (3.22%) deep infections. The ankle joint arthrosis as a late complication appeared in 4 (12.90%) patients. All arthroses appeared in patients who had type C fractures. The final functional results based on the AOFAS score were excellent in 51.61%, good in 32.25%, average in 12.90% and bad in 3.22% of the patients. Conclusion. External skeletal fixation and minimal internal fixation of distal tibial pilon fractures is a good method for treating all types of inta-articular pilon fractures. In fractures types B and C dynamic external skeletal fixation allows early mobility in the ankle joint. Key words: tibial fractures; orthopedic procedures; external fixators; internal fixators; treatment outocme.